Hybrid teaching and learning: A conjoint analysis of student preferences in online and onsite scenarios - Feubli, Patricia; MacKevett, Douglas; Schwarz, Jürg (Journal of computer assisted learning, 2024)
Background This research paper presents a cross‐sectional study that examinefs the preferences of students for hybrid teaching and learning scenarios. Unlike previous studies that merely describe hybrid scenarios, this research prioritizes them, offering evidence‐based findings for informed policy decisions. Methods The data collection method involved eight choice‐based tasks using the conjoint analysis technique conducted with ‘Sawtooth’ software. The study surveyed students at a mid‐sized university across four departments in Central Switzerland. The sample analysed in this article comprised 319 respondents from the Lucerne School of Business. Results and Conclusions Our survey found that students' own location during a teaching session played a significant role in determining participation preferences, followed by that of the lecturer. Factors that influenced students' preferences whether to attend onsite or online include workload, didactical format, perceived level of difficulty, student residence, and semester. Forms of hybrid collaboration and student–student interaction did not significantly influence student preferences. Takeaways The value of this study lies in its evidence‐based findings for specific hybrid scenarios, which can provide useful insights for policymakers in degree programs and faculty in hybrid classrooms. This study is one of only a few to use conjoint analysis with such a high respondent rate to determine student preferences for hybrid attendance. Lay Description What is currently known about this topic? Student demand for hybrid teaching scenarios remains high, while many faculty find the scenario technically challenging. Opinions as to the precise features of ‘hybrid’ vary widely. No clear understanding of the conditions under which students will decide to attend any given class. Demand for additional exchange among online students is recommended in the literature, but often not implemented. What does this paper add? The study uses conjoint analysis to simulate how students make attendance decisions. The study shows empirically which factors are most important to determine students' attendance. Two‐thirds of the students surveyed prefer an online option. Group composition and informal exchange do not significantly impact students' attendance preferences. Implications for practice/or policy Students appreciate the flexibility of online learning but expect lecturers to be onsite. Difficult subjects are more likely to be attended onsite. Student residence, workload, degree program, and semester impact students' attendance preferences. No additional infrastructure is needed to encourage exchange among students.